2014
DOI: 10.1007/s00430-014-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis: the effectiveness of the cysticidal treatment could be influenced by the host immunity

Abstract: Neurocysticercosis, a clinically and radiologically pleomorphic parasitic disease, is still endemic to most non-developed countries of Latin America, Africa, and Asia. Anti-helminthic drugs (AHD) are generally effective and rapidly destroy parenchymal cysticerci. In contrast, several cycles of AHD are frequently necessary to damage extraparenchymally located parasites. The present study was designed to evaluate whether differences in the immunological profile of the patients is involved in the diversity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The previously reported Treg differentiation in vitro driven by cysticerci supports this possibility [17]. Additionally, the inflammatory immune response influences both clinical manifestations in NC patients [9,16,18,26] and the response to cysticidal treatment, possibly related with higher IL-17 and IL-6 levels [9]. In concordance with this, we found lower IL-6 levels in resistant patients with respect to controls.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The previously reported Treg differentiation in vitro driven by cysticerci supports this possibility [17]. Additionally, the inflammatory immune response influences both clinical manifestations in NC patients [9,16,18,26] and the response to cysticidal treatment, possibly related with higher IL-17 and IL-6 levels [9]. In concordance with this, we found lower IL-6 levels in resistant patients with respect to controls.…”
Section: Discussionsupporting
confidence: 80%
“…Most of these NC patients show higher central Treg percentages, which positively correlated with Treg peripheral levels [14]. These cell subtypes tightly control inflammation, and it has been proposed that an inflammatory status is required for the cysticidal treatment to be effective [9]. Considering the influence of catecholamines on the inflammatory response, we focused on cysticidal treatment resistant-NC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a radiological level, although most parasites were racemose, about 20% of patients presented a single parasite. The consequences of this variability are not completely understood, but it could be involved in the heterogeneity of the response to treatment and in the varying success of such treatment, as previous studies indicate [44, 45]. Further analysis is required to better understand this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cardenas et al detected differential expression of immune-response genes in Taenia -antigen stimulated peripheral blood mononuclear cells from NCC patients who did or did not demonstrate radiological response to anti-helminthic drug treatment [10]. It has also been reported that the network of monocytes and astrocytes play a role in the inflammatory response to intraparenchymal cysts of NCC [11, 12]. Furthermore, other studies show that blood monocytes produce bioactive mediators including CXCL8 (IL-8), CCL2 (MCP-1) and TNF-α, in response to stimulation with T .…”
Section: Introductionmentioning
confidence: 99%